Efficacy of the early start Denver model combined with the TEACCH program in children with autism spectrum disorder - Ma, Ling-Ling; Lv, Qian-Qian; Xiao, Yao (Frontiers in Psychiatry, 2025)
BackgroundEarly intervention plays a crucial role in improving outcomes for children with autism spectrum disorder (ASD). The Early Start Denver Model (ESDM) and the Treatment and Education of Autistic and Communication-Handicapped Children (TEACCH) program are commonly used approaches. This study aimed to evaluate whether combining ESDM with TEACCH provides greater clinical benefits than ESDM alone in young children with ASD.MethodsA retrospective observational study was conducted involving 264 children aged 24–60 months diagnosed with ASD. Participants were divided into two groups based on treatment period: the control group (n = 128) received ESDM-only therapy, while the observation group (n = 136) received ESDM combined with TEACCH over six months. Outcomes were assessed using the Autism Treatment Evaluation Checklist (ATEC) and the Psycho-Educational Profile, Third Edition (PEP-3). Baseline comparability was confirmed by the Chinese version of the Childhood Autism Rating Scale (CCARS).ResultsBoth groups showed significant within-group improvement after intervention, but the combined observation group demonstrated greater gains. Post-treatment ATEC scores decreased from 84.56 ± 20.90 to 68.76 ± 17.96 versus 92.84 ± 18.20 to 84.91 ± 17.50 in controls (between-group difference = 16.32 ± 4.35; P < 0.001; Hedges’ g = 0.45). Cognitive scores on the PEP-3 improved by 11.31 points in the observation group compared to 8.15 in controls (P = 0.026). Reductions in maladaptive behaviors also favored the combined intervention (P = 0.036).ConclusionsThe integrated ESDM and TEACCH intervention was more effective than ESDM alone in enhancing cognitive development and reducing symptom severity in young children with ASD.